MENGGALI KEARIFAN LOKAL; TRADISI TOET APAM SEBAGAI BUDAYA YANG BERKONTRIBUSI TERHADAP SOSIALISASI DAN HUBUNGAN ANTARWARGA DESA BEUREULEUNG KECAMATAN GRONG-GRONG KABUPATEN PIDIE - Nufus, Nazhatun; Saputri, Yuni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2025)
Teut Apam is a tradition that has been practiced for generations by the people of Pidie Regency. In ancient times, this tradition was very Islamic. As time went by, this tradition underwent changes. The aim of this research is to explain the Teut Apam tradition in the village of Beureuleung, Grong Grong District, Pidie. This research also aims to determine the extent to which the Toet Apam culture contributes to socialization and relationships among residents. This research uses a qualitative method. Data collection was carried out through observations, interviews, and relevant literature studies. The results show that Khanduri Apam has an influence on the social life of the community because Khanduri Apam is considered a worship act, especially as a donation; furthermore, the Teut Apam tradition also brings happiness to both those who perform it and those who receive the donations. For the people of Beureuleung Village, the Teut Apam tradition has become a cultural practice that is passed down from generation to generation, and they designate the month of Ra'jab as the month for the implementation of this tradition.Keywords: Traditions;Teot Apam;Culture